Coordination of Europe’s climate-related knowledge base: Networking and collaborating through interactive events, social media and focussed groups - Chris Hewitt (Elsevier, 2021)
Knowledge of the climate is essential to manage climate-related risks. Underpinning this knowledge is a huge range of climate research and climate service activities. There has been a marked expansion of such activities and while the numerous and diverse funding streams, activities and organizations involved means that climate service development is relatively well resourced in places, there is a risk that the landscape becomes fragmented, duplicative, confusing, and inefficient. To mitigate this, the European Commission established the Climateurope project to bring coordination to Europe’s climate-related knowledge base. Climateurope created a managed network to share knowledge, improve synergies and reduce fragmentation among the stakeholders. As the network evolved, we proactively strove for equality, diversity and inclusion, for example for gender, under-represented regions, and under-represented stakeholder groups. Climateurope explored and adopted innovative approaches to engaging the network members, including face-to-face networking events (Festivals), virtual networking events (Webstivals and webinars), use of arts, social media, expert groups, publications, and an active website. The mix and integration of the traditional communications, such as website, publications and expert groups, with more innovative and varied approaches, such as the Festivals, Webstivals, social media and arts, proved popular and successful in making the network active and attractive. We describe how the network and collaboration was established and managed, and we offer some recommendations for others based on our experiences, including consideration of equality, diversity and inclusion, consider strategies for growing, managing and sustaining the network, and consider a mix of virtual and physical networking events.